Modified tension infiltrometer and its use to determine the unsaturated hydraulic conductivity of upper vadose zone - Sattar, Golam Shabbir (Journal of Nepal Geological Society, 1998)
A modification of the CSIRO type tension infiltrometer was designed (designated UNCEL type) and tested. This infiltrometer is considerably cheaper, but more versatile, than any other infiltrometer reported so far. The modified infiltrometer was used in a reconstructed vadose zone to measure the unsaturated hydraulic conductivity and effect of compaction associated with the upper vadose zone. Hydraulic conductivity, a function of matric potential, is a fundamental property for water entry into the soil as well as in the upper vadose zone. Tension infiltrometer technique for determining unsaturated hydraulic conductivity, which is also a function of soil water pressure head, was compared with the existing techniques. The analysis of data from tension infiltrometer is based mainly on flow rate at steady-state condition. The steady-state measurement also enables to determine unknown parameters on the basis of at least two negative heads at the same location. This modified infiltrometer imposes pressure potentials at soil surface from 0.01 to 0.15 m of water, as a result macropores with an air entry value of less than applied tension are excluded. This is practically useful when investigating the influence of structure and compaction of upper vadose zone. Measurement of infiltration at various negative pressure head, with a single disc diameter allowed sensitive measurement of hydraulic properties of upper vadose zone with minimal surface disturbance. The newly designed tension infiltrometer and adopted schemes of calculation enable to determine unsaturated hydraulic conductivity of upper vadose zone with relevance to structural effects more accurately.